(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The company’s ability to generate profits must be high so that the company can continue to run its business. The ability to generate profits is called profitability. Profitability can be increased one of them by adding funds. Sukuk in Indonesia has now become one of the alternative sharia fund withdrawals that are of interest to the company. Sukuk are issued using different contracts. The diversity of the types of contracts that underlie sukuk certainly has different advantages. The diversity of sukuk contract types and their effects on profitability is the research objective to be achieved in this study. The study was conducted with an explanatory method. Data collected for profitability is secondary in the form of return on assets (ROA) collected from the financial statements of companies that issue sukuk. While the types of sukuk are also taken from sukuk statistical data published by the Indonesian stock exchange. Data were analyzed using chi square. The results showed that the type of sukuk affects the company and ultimately affects the profitability of the company.